Bioaccessibility of Flavones, Flavanones, and Flavonols from Vegetable Foods and Beverages - Alice Cattivelli; Melissa Zannini; Maddalena De Angeli; Domenico D’Arca; Vincenzo Minischetti; Angela Conte; Davide Tagliazucchi (Biology)
The bioaccessibility of flavonoids is of paramount importance in determining their bioavailability and biological effects. Bioaccessibility is influenced by several aspects, comprising the food matrix and the structure of flavonoids. In the present study, the bioaccessibility of different classes of flavonoids (flavanones, flavones, and flavonols) was investigated after in vitro gastro-intestinal digestion of beverages and vegetables. O-glycosylated flavanones were stable during in vitro digestion and easily released from the food matrix. Otherwise, C-glycosylated flavanones displayed a lower bioaccessibility index. Similarly, flavones exhibited a high bioaccessibility index in beverages and vegetables, with the O-glycosylated forms being more stable than the C-glycosylated. Flavonols displayed different stability under gastro-intestinal conditions depending on their structure. The presence of a catechol moiety in the B-ring, as observed in 3-O-glycosylated quercetins, negatively impacted flavonol stability in comparison with kaempferol derivatives that lack the catechol moiety. Indeed, the presence of more than one sugar or the glycosylation of the OH group in the B-ring improved the digestive stability of quercetin derivatives. For flavonols, a clear food matrix effect was observed by comparing the bioaccessibility in beverages and vegetable foods. These findings may aid in improving the comprehension of the biological effects of flavonoids and flavonoid-rich foods.